Structure of Plankton and Bentos Communities in Bahorok River in Bahorok District, Langkat Regency, North Sumatra - Wahyuningsih, Hesti; Barus, Ternala Alexander; Pardosi, Sinta R; Mustaqilla, Safira; Atni, Oky Kusuma; Nasution, Ahmad Luthfi Abdillah; Hermansyah; Mardhatillah, Siti; Lubis, Putri Amelia (International Journal of Ecophysiology, 2024)
This study analyzed the diversity and abundance of plankton and benthos in the Bahorok River, Bukit Lawang, Langkat Regency, North Sumatra Province. This study was conducted on May 25, 2024. Sampling was done by collecting filtered water using a plankton net and substrate using a surber net to collect benthos from two points in the river. Identification of plankton and benthos using a microscope and laboratory analysis for physicochemical parameters. The value of plankton diversity in the Bahorok River was indexed well with a value of 3.01 as well as good evenness with a value of 0.95 however, benthos diversity was indexed low with a value of 0.68 and evenness was indexed moderate with a value of 0.62. The highest type of plankton is Raphidiopsis raciborskii. The highest type of benthos is Progomphus sp.